The Disraeli Roads of Anfield, Urban Renewal and Sporting Culture - Ben Williams (Cahiers Victoriens et Edouardiens)
At the tail end of the Victorian era, professional football was an emerging cultural development within British society. Expanding industrial cities such as Liverpool subsequently saw the emergence of large footballing venues typified by Anfield football stadium (built 1884), which would become a dominant feature of the residential northern suburb of Anfield within the eponymous city location. The Anfield district also became demographically notable for its large swathe of terraced housing, constructed at approximately the turn of the nineteenth/twentieth centuries, surrounding the stadium in all directions. Amidst this redbrick housing of varying types and sizes, five sequential roads were constructed in proximity to this sporting arena with distinctively significant names in the context of the life of Benjamin Disraeli; being all named in memorial of Disraeli novels. The continued presence of such road names is a notable if at times innocuous reflection of Disraeli’s legacy for the urban and cultural equilibrium of everyday cultural and social life in Britain. This article seeks to analyse the evolving dynamics within such communities across generations, and how the legacy and theme of Victorian urban renewal continues to exist within contemporary society, yet often without wider public consciousness of such Disraelian heritage.